PERLINDUNGAN HUKUM TERHADAP PEKERJA/ BURUH DI TINJAU DARI ASPEK HUKUM JAMINAN SOSIAL TENAGA KERJA - PINE MARBUN; LULUSOKHI MANAO; YUSUF ELIM BARTA HARIANJA; CITRA INDAH LESTARI SIMANGUNGSONG (LP2MTBM MAKARIOZ, 2020)
The main objective of BPJS Ketenagakerjaan is certainly to provide social security and protection for workers throughoutIndonesia. Through its various programs, BPJS Ketenagakerjaan strives to provide certainty of protection and social welfarefor all Indonesians. The impact of employer non-compliance is very detrimental to workers, as happened in the mancisfactory fire in 2019 in Langkat Binjai, Provinisi North Sumatra. Out of a total of 103 employees, only 27 were registered withBPJS Ketenagakerjaan. As a result of the fire incident, it is not known that the employee died but only 3 people areregistered as participants of BPJS Ketenagakerjaan. The crash of a private airline in November 2018 that killed all cabincrew and passengers, it is known that the pilot and flight attendant who died were registered with BPJS Ketenagakerjaanwith lower wages. This has an impact on work accident compensation that is given less than the value it should be. In fact,there are still employers who have not complied, participated in bpjs employment only part of the program, not all workersare registered or reporting lower wages than they actually are. Few employers think of social security as just a financialburden. The impact of employer non-compliance is very detrimental to workers, as happened in the mancis factory fire in2019 in Langkat Binjai, Provinisi North Sumatra. Out of a total of 103 employees, only 27 were registered with BPJSKetenagakerjaan.